Passive UHF RFID tag velocity approximation using linear phased array - Balon, Siegfred D.
The project devised a scheme on detecting the velocity of the RFID passive tag operating at UHF band. It was aimed to detect the velocity of a tag mounted on a mobile object and the reader infrastructure stationary at a particular place, for example, tags on the cars and the reader at the roadside. A beam-forming antenna array was used to improve the reading capability of the reader and to do the localization. The reader antenna was implemented as a linear phased array that electronically steers a beam utilizing a programmable phase shift network. Scanning of tags and comparison of the tag position with time was made to determine the tag velocity. The array was built using patch antennas. The scope of the project included the design of the reader beam-forming antenna array and the host software to manage the data. The project deployed a typical RFID setup consisting of reader-middleware, reader antennas, a host personal computer, and the tags on field. The base reader platform used was the ALIEN ALR-9800 UHF RFID Reader operating at 902-928 MHz. In the long run, the project has the potential to be developed to aid systems in real-world traffic management wherein velocity of tagged vehicles can be determined. It can be used on applications such as individual vehicle velocity detection, traffic condition sensing, and detection of traffic violations: beating the red light, against the flow of traffic, and overstaying on loading/unloading areas.